Long-term follow-up of peripheral lymphocyte subsets in a cohort of multiple sclerosis patients treated with natalizumab. (24th April 2014) - Koudriavtseva, T; Sbardella, E; Trento, E; Bordignon, V; D'Agosto, G; Cordiali-Fei, P
Summary: Natalizumab, an anti-alpha4 integrin monoclonal antibody inhibiting the adhesion of lymphocytes to the endothelium, is a widely accepted drug treatment for relapsing–remitting multiple sclerosis (RRMS). A peripheral increase of T and B lymphocytes has already been observed as an early treatment effect. This retrospective observational study was aimed to evaluate the peripheral lymphocyte subsets during a long-term treatment follow-up. We included 23 RRMS patients treated with natalizumab for at least 24–48 months who had pretreatment lymphocyte evaluation. Baseline values of lymphocyte subsets and CD4/CD8 ratio did not differ significantly from the 23 matched healthy subjects. The periodic (every 3–6 months) assessment of immune cell subsets was performed by flow cytometry on peripheral blood collected before drug injection. Therapy with natalizumab was confirmed to be effective during the observational period. For all patients, the increase in lymphocytes during natalizumab therapy compared to baseline at every assessment was significantly higher compared to that of overall white blood cells (2·1- and 1·3-fold, respectively, P  < 0·0001). Both T cell subsets were proportionally modified and the CD4/CD8 ratio did not change significantly, while B cells increased significantly compared to T and NK cells (3·2-, 1·88- and 1·92-fold, respectively, P  < 0·0001). These changes remained constant throughout the 25–48-month period of therapy. In conclusion, effective natalizumab treatment of RRMS patients was associated with the persistence of its biological effects through a stable increase of peripheral lymphocytes, mainly B cells, and an unchanged proportion of T cell subsets in long-term follow-up.